Combining 3D Printing and Printable Electronics - Sarik, John; Butler, Alex; Villar, Nicolas; Scott, James; Hodges, Steve (Proceedings of TEI 2012 Works in Progress, 2012)
A platform that enables the integration of conductive traces and printed three dimensional mechanical structures has been developed. We discuss the development of the platform and address issues that arise when combining 3D printing and printable electronics. We demonstrate a rapid prototyped three dimensional conductive trace and propose future applications for the platform.